Research on MPDPC with FADRC control strategy for three-phase rectifying converter. (July 2022) - Zhao, Yulian; Liu, Hemiao; Ding, Chao; Cheng, Yanming; AL Shurafa, Mahmoud AM; Wu, Jing; Lee, Ilkyoo; Niu, Jing; Wang, Zhongwei; Yao, Lu
Due to unpredictable factors, the model predictive direct power control (MPDPC) exists weak robustness when the parameters change of three-phase rectifying converter. Therefore, this paper introduced Fractional Active Disturbance Rejection Control (FADRC) into the MPDPC system to improve the robustness of rectifying converter, that is, the power loop of PID controller in conventional model predictive control is replaced by FADRC. In order to verify the effectiveness of the proposed control strategy in this paper, a model of three-phase rectifying converter is established in MATLAB, and the simulation is conducted. Compared with the control effects of the MPDPC with PID (MPDPC-PID) control strategy and MPDPC with Linear Active Disturbance Rejection Control (MPDPC-LADRC) under different operational scenarios, the simulation results demonstrate that the MPDPC with FADRC (MPDPC- FADRC) strategy has best disturbance rejection capability, robustness and rapidity, and it can significantly reduce the voltage fluctuation of DC bus. This study can provide a valuable guidance and reference for the design of the efficient and stable three-phase rectifying converter.